Efektivitas Iklan Meatless Kingdom pada Media Sosial Instagram dengan Pendekatan Model AIDA - Azzahra, Sheila Najwa; Hapsari, Hepi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Instagram is one of the largest social media platforms in Indonesia and is widely used by companies to reach consumers directly, including Meatless Kingdom, a producer of plant-based food products. Despite offering health and environmental benefits, the product still faces challenges such as low public awareness and limited interest in trying plant-based alternatives. This study aims to measure the effectiveness of Meatless Kingdom’s promotional content on Instagram using the AIDA model (Attention, Interest, Desire, Action). The research employed a quantitative descriptive survey method involving 100 active followers of the @meatlesskingdom Instagram account, selected through systematic random sampling. Additional data were collected through interviews with the business owner and a literature review. The findings indicate that the promotional content is categorized as “Highly Effective” with an average score of 4.372. The highest scoring dimension was Interest (4.4975), followed by Attention (4.396), Action (4.3025), and Desire (4.292) as the lowest. Meatless Kingdom is encouraged to enhance emotional branding by maintaining appealing visuals and narratives that emphasize health, sustainability, and a modern lifestyle to boost consumer engagement and loyalty.